2017
DOI: 10.4269/ajtmh.16-0849
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Natural Infection of Phlebotomus sergenti with Leishmania tropica in a Classical Focus of Leishmania major in Tunisia

Abstract: In Tunisia, chronic cutaneous leishmaniasis due to is an important health problem. Its spreading has not been fully elucidated. Information on sandfly vectors, as well as their associated species, is of paramount importance since vector dispersion is one of the major factors responsible for pathogen dissemination. Ninety-seven unfed females belonging to the genera and were collected between June and August 2015 using sticky paper traps. Polymerase chain reaction-restriction fragment length polymorphism analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These lesions are distinguished by their chronicity and long duration of development [37,38]. Its causal agent, L. tropica [27,39] Figure 2) [47,48] and in human cases [47] of the same region confirms the vectorial role of this species in the transmission of L. tropica in Tunisia. Indeed, P. sergenti is the proven vector of L. tropica in the Middle East and Morocco [14,42].…”
Section: Leishmaniasis Due To L Tropica Zymodeme Mon-08mentioning
confidence: 87%
“…These lesions are distinguished by their chronicity and long duration of development [37,38]. Its causal agent, L. tropica [27,39] Figure 2) [47,48] and in human cases [47] of the same region confirms the vectorial role of this species in the transmission of L. tropica in Tunisia. Indeed, P. sergenti is the proven vector of L. tropica in the Middle East and Morocco [14,42].…”
Section: Leishmaniasis Due To L Tropica Zymodeme Mon-08mentioning
confidence: 87%
“…There is need for novel molecular tools to respond to challenges associated to leishmaniases and continuous changes in their epidemiology at local and global levels [12,20,21,66]. Indeed, molecular tools are instrumental to define strategies for disease control as they allow PLOS NEGLECTED TROPICAL DISEASES alternative of choice to laborious, costly and time consuming MLEE methods [25,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Sergentomyia is believed to transmit lizard Leishmania species whereas Phlebotomus transmit human pathogenic species of Leishmania [30]. However, studies in Ghana and elsewhere have suggested the possible involvement of Sergentomyia minuta, Sergentomyia ingrami, Sergentomyia hamoni and Sergentomyia darlingi as vectors of leishmaniasis [29,[31][32][33]. This reiterating the fact that some Sergentomyia species disclose periodic or opportunistic anthropophilic feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%